ANALISIS KEMAMPUAN PESERTA DIDIK KELAS XI MIA SMA DI KABUPATEN ENREKANG DALAM MENYELESAIKAN SOAL-SOAL BERDIMENSI PENGETAHUAN FAKTUAL, KONSEPTUAL, PROSEDURAL DAN METAKOGNITIF - Ilham Assidiq (Chemistry Education Review (CER), 2017)
This descriptive research aims to discover the students’ ability in solving question in Factual, Conceptual, Prosedural and Metacognitive dimension in class XI MIA of Senior High School in Enrekang District. The population of the research was all of the students class XI MIA of Senior High School in Enrekang Discrict which consisted of 39 classes with the total 907 students. The sample of the research was selected by using stratified purposive random sampling technique and obtained SMA 1 Alla, SMA 1 Anggeraja, SMA 1 Baraka, SMA Masalle and SMA Muhammadiyah Kalosi, 5 classes with the total 150 student. The instrument of the research were questionnaire and learning result test. The result of the research show that (i) the ability of the students in solving the question in factual dimension is in sufficient category; conceptual dimension is in low category; procedural dimension is in low category; metecognitif dimension is in very low category in class XI MIA of Senior High School in Enrekang Discrict; (ii) there is no difference in the achievement of factual, conceptual, and procedural ability of the school in the city or in the main road with the school in the suburb (out of town) and the favorite schools with non-favorite school; (iii) there are difference in the achievement of metacognitif ability of the school in the city or in the main road with the school in the suburb (out of town) and the favorite schools with non-favorite school; (iv) there are difference of the students’ leaning result of the school in the city or in the main road with the school in the suburb (out of town) and the favorite schools with non-favorite school.